2021
DOI: 10.1002/jia2.25841
|View full text |Cite
|
Sign up to set email alerts
|

The likelihood of severe COVID‐19 outcomes among PLHIV with various comorbidities: a comparative frequentist and Bayesian meta‐analysis approach

Abstract: IntroductionThe SARS‐CoV‐2 virus can currently pose a serious health threat and can lead to severe COVID‐19 outcomes, especially for populations suffering from comorbidities. Currently, the data available on the risk for severe COVID‐19 outcomes due to an HIV infection with or without comorbidities paint a heterogenous picture. In this meta‐analysis, we summarized the likelihood for severe COVID‐19 outcomes among people living with HIV (PLHIV) with or without comorbidities.MethodsFollowing PRISMA guidelines, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In this study, having diabetes, hypertension, chronic kidney disease, tuberculosis, and malignancy were all associated with an increased risk of in-hospital mortality. In addition, several meta-analyses have showed a high rate of comorbidities in PWH and an increase in risk of severe disease and mortality from COVID-19 as total number of comorbidities increased [44 ▪▪ ,45].…”
Section: Comorbidities Social Determinants Of Health and Coronavirus ...mentioning
confidence: 99%
“…In this study, having diabetes, hypertension, chronic kidney disease, tuberculosis, and malignancy were all associated with an increased risk of in-hospital mortality. In addition, several meta-analyses have showed a high rate of comorbidities in PWH and an increase in risk of severe disease and mortality from COVID-19 as total number of comorbidities increased [44 ▪▪ ,45].…”
Section: Comorbidities Social Determinants Of Health and Coronavirus ...mentioning
confidence: 99%
“…Although initial small studies suggested that PLWH did not exhibit worse outcomes during acute SARS-CoV-2 infection [55][56][57][58][59], larger studies have shown that HIV status is a risk factor for severe outcomes even among the virologically suppressed [60][61][62][63][64][65][66][67]. This risk is most pronounced in those with comorbidities, viremia, and/or poor immune reconstitution [63,[68][69][70][71][72]. Second, PLWH commonly exhibit metabolic comorbidities such as diabetes and obesity, as well as cardiovascular disease [73][74][75][76][77][78][79][80][81], which are also risk factors for Long COVID.…”
Section: Risk Factors For and Mechanisms Of Long Covid: Why People Li...mentioning
confidence: 99%
“…Our colleagues Bajpai et al. have submitted a Letter to the Editor regarding our recently published meta‐analysis “The likelihood of severe COVID‐19 outcomes among PLHIV with various comorbidities: a comparative frequentist and Bayesian meta‐analysis approach [ 1 ].” We appreciate their feedback and request for clarification and would like to respond to their letter.…”
Section: Tablementioning
confidence: 99%
“…stressed the fact that their conditional predictive ordinates approach [ 4 ], compared to methods described by Gelfand and Ghosh [ 5 ], only evaluates the posterior predictive probability density but does not simulate from it, and both methods relied on applying posterior predictive distribution. Also, in our sensitivity analysis, we checked the prior predictive cumulative distribution function (CDF, as stated in Figure S5 of the Supporting Information of [ 1 ]). The CDF is a probability, and the probability density function (PDF) is the derivative of the CDF, and the predictive distribution function is a probability as well.…”
Section: Tablementioning
confidence: 99%